Analysis of Pork Adulteration In Recycled Frying Oils Using Raman Spectroscopy - Ghazali, Haizatul Hadirah; Tukiran, Nur Azira (Sciendo, 2021)
Unscrupulous food business operators may use recycled frying oil to save costs. Of particular concern is the recycled frying oil is usually taken from non-halal food premises which should not be used by halal food premises, and indeed may posing health treats to consumers. Hence, the objective of this paper is to analyse pork adulteration in recycled frying oils by using the combination of Raman spectroscopy and Principal Component Analysis (PCA). Samples of frying oils from homemade fried pork, fried chicken, fried fish and fried banana were analyzed. Spiked samples were prepared by adding frying oil from homemade fried pork ranging from 10% to 50% (v/v) to frying oils from homemade fried chicken, fried fish and fried banana. The results found that Raman spectroscopy and PCA are able to differentiate adulterated frying oil and unadulterated frying oils. However, it could not distinguish the percentage of pork adulteration in the spiked samples. This method would beneficial to ensure food integrity in the frying oils.